REKONSTRUKSI PENDEKATAN SUPERVISI PENDIDIKAN BERBASIS HUMANISTIK DAN KINERJA DALAM MENYONGSONG GENERASI ALPHA DI INDONESIA - Zaskia (Jurnal Riset Multidisiplin Edukasi, 2026)
Changes in the characteristics of students belonging to Generation Alpha require a new approach to managing and improving the quality of education, including in the practice of educational supervision. Educational supervision, which has tended to be administrative and evaluative in nature, is considered to be insufficient in responding to the challenges of learning that are increasingly complex, adaptive, and technology-based. This study aims to reconstruct the approach to educational supervision by integrating humanistic and performance-based approaches as a strategic effort to meet the educational needs of Generation Alpha in Indonesia. This study uses the library research method by analyzing various scientific sources in the form of books, journal articles, and relevant educational policy documents. The results of the study show that the humanistic supervision approach plays an important role in building empathetic, dialogical, and empowering professional relationships with teachers, while performance-based supervision is necessary to ensure accountability and the achievement of learning quality standards. The integration of these two approaches allows educational supervision to function in a balanced manner as a means of professional development and quality assurance. The reconstruction of adaptive, contextual, and performance-oriented educational supervision is considered relevant to improving the quality of learning and preparing a competent, characterful, and intelligent Generation Alpha.